2004
DOI: 10.1097/01.ta.0000078883.74947.eb
|View full text |Cite
|
Sign up to set email alerts
|

Children in Side-Impact Motor Vehicle Crashes: Seating Positions and Injury Mechanisms

Abstract: Severe injuries to near-side occupants occurred in both the presence and absence of compartment intrusion. A typical pattern of head, chest, and extremity injury similar to that seen among child pedestrians was observed among near-side child occupants in side-impact crashes. The center seat was statistically safer than the near-side seat, particularly for restrained child occupants. Scene information may be useful to trauma teams for the prediction of injury type and location. Avoiding intrusion and preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 12 publications
1
16
0
3
Order By: Relevance
“…[38][39][40][41][42][43] Although a child must never be carried on someones lap, 42 even in the backseat, this is a common habit in Brazil. Based on classic physics, one may affirm that in a head-on crash at 50 km per hour into a hard object, a child weighing 10 kg may produce a force as heavy as half a ton against the arms of the person who is holding him/her.…”
Section: Safe Transportation Of Children and Adolescentsmentioning
confidence: 99%
“…[38][39][40][41][42][43] Although a child must never be carried on someones lap, 42 even in the backseat, this is a common habit in Brazil. Based on classic physics, one may affirm that in a head-on crash at 50 km per hour into a hard object, a child weighing 10 kg may produce a force as heavy as half a ton against the arms of the person who is holding him/her.…”
Section: Safe Transportation Of Children and Adolescentsmentioning
confidence: 99%
“…These facts point to the importance of improving the injury mitigation for children in side impacts. Side-impact injury risk and injury pattern for child occupants has been described in several studies Arbogast, Jermakian, et al 2005;Arbogast et al 2001;Howard et al 2004;Maltese et al 2005Maltese et al , 2007Orzechowski et al 2003;Scullion et al 2008;Starnes and Eigen 2002). These studies highlight the head as the most frequently injured body region among children up to 15 years of age.…”
Section: Introduction Backgroundmentioning
confidence: 90%
“…Further, the injury rate has been shown to vary by seating position. The AIS2+ injury rate is significantly higher in near-side impacts than in center or far-side impacts Howard et al 2004;Starnes and Eigen 2002). The principal mechanism of injury is contact with the vehicle interior, mainly associated with intrusion into the occupant compartment at the child's position and/or lateral translation of the child's body (Howard et al 2004).…”
Section: Introduction Backgroundmentioning
confidence: 97%
“…Another is due to the kinematics of side impact crash which depends upon both the magnitude of the impulse from the bullet vehicle and its principle direction of force (PDOF) impacting angle [8]. In addition, it has been shown that the head contact with intruding door due to the bullet vehicle plays a pivotal role and has to be considered in addressing any mitigation efforts [9,10].…”
Section: Introductionmentioning
confidence: 99%